2014
DOI: 10.1183/09031936.00087114
|View full text |Cite
|
Sign up to set email alerts
|

Riociguat for the treatment of chronic thromboembolic pulmonary hypertension: a long-term extension study (CHEST-2)

Abstract: Riociguat is a soluble guanylate cyclase stimulator approved for the treatment of inoperable and persistent/recurrent chronic thromboembolic pulmonary hypertension (CTEPH). In the 16-week CHEST-1 study, riociguat showed a favourable benefit-risk profile and improved several clinically relevant end-points in patients with CTEPH. The CHEST-2 open-label extension evaluated the long-term safety and efficacy of riociguat.Eligible patients from CHEST-1 received riociguat individually adjusted up to a maximum dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
209
0
32

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(246 citation statements)
references
References 23 publications
5
209
0
32
Order By: Relevance
“…Treatment with riociguat improved QoL in patients with inoperable CTEPH or persistent CTEPH after surgery. 30, 31 The present study is the first to show improvement in QoL on SF-36v2 in patients with CTEPH treated nonsurgically. The SF36v2, however, is not a perfect tool for evaluating QoL in CTEPH patients.…”
Section: Discussionmentioning
confidence: 96%
“…Treatment with riociguat improved QoL in patients with inoperable CTEPH or persistent CTEPH after surgery. 30, 31 The present study is the first to show improvement in QoL on SF-36v2 in patients with CTEPH treated nonsurgically. The SF36v2, however, is not a perfect tool for evaluating QoL in CTEPH patients.…”
Section: Discussionmentioning
confidence: 96%
“…Riociguat was generally well tolerated in both the PATENT and CHEST studies, and safety and tolerability results for all 4 studies have been published previously. 10,11,17,18 In summary, the most common adverse events were headache, dyspepsia, peripheral edema, nausea, dizziness, diarrhea, nasopharyngitis, and vomiting. Drug-related serious adverse events were reported in 2.4% of patients receiving riociguat 2.5 mg 3 times daily in PATENT-1 and in 3.5% of patients receiving riociguat in CHEST-1.…”
Section: Phase 3 Trialsmentioning
confidence: 99%
“…PATENT-2 (NCT00863681) and CHEST-2 (NCT00910429) were long-term, single-arm extensions to PATENT-1 and CHEST-1, respectively, in which all patients (including those previously randomized to placebo) received open-label riociguat. [17][18][19][20] Detailed methodology and trial designs have been published previously. The institutional review board at each participating center approved the trial protocols.…”
Section: Phase 3 Trialsmentioning
confidence: 99%
“…These studies have shown that riociguat can improve exercise capacity, hemodynamic function, and quality-of-life parameters in patients with PAH or CTEPH. [5][6][7][8] Data from the clinical trial program have also shown riociguat to be well tolerated and to have a favorable safety profile that was sustained over long-term treatment. Most of the observed side effects are consistent with the vasodilatory effects of the drug, such as headache, dizziness, and hypotension, and adverse events were evenly matched between riociguat and placebo treatment groups.…”
mentioning
confidence: 99%
“…Few patients discontinued treatment as a result of adverse events. [5][6][7][8][9][10] On the basis of these studies, riociguat was the first therapy to be approved for the treatment of two indications: PAH, as demonstrated in patients with etiologies of idiopathic or heritable PAH or PAH associated with connective-tissue disease, and inoperable or persistent/recurrent CTEPH. 9,10 Patients with congenital heart disease were also included in the PATENT studies.…”
mentioning
confidence: 99%